2018
DOI: 10.3892/ol.2018.8388
|View full text |Cite
|
Sign up to set email alerts
|

Fisetin inhibits the proliferation of gastric cancer cells and induces apoptosis through suppression of ERK 1/2 activation

Abstract: The present study aimed to investigate the effect of fisetin on proliferation and apoptosis of gastric cancer cells, as well as the underlying mechanism. Proliferation in SGC7901 cancer and GES-1 normal cells was analyzed using a CCK-8 assay. Apoptosis was analyzed using an Annexin V/Propidium Iodide apoptosis kit and phosphorylation of extracellular signal-regulated kinase (ERK) 1/2 was analyzed by western blot assay. Treatment of SGC7901 cells with various concentrations (1, 5, 10, 15 and 20 µM) of fisetin f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…Similar to previous reports [ 36 , 37 , 38 , 39 ], the flavonoids fisetin and quercetin were active in stimulating ERK1/2 phosphorylation in OC cells. In contrast, others have claimed that the apoptosis-inducing function of fisetin and quercetin is mediated through ERK1/2-signaling inhibition [ 40 , 41 ], accompanied by ROS generation [ 42 ]. The differences in the outcome of ERK activation are probably due to differences in cellular content.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to previous reports [ 36 , 37 , 38 , 39 ], the flavonoids fisetin and quercetin were active in stimulating ERK1/2 phosphorylation in OC cells. In contrast, others have claimed that the apoptosis-inducing function of fisetin and quercetin is mediated through ERK1/2-signaling inhibition [ 40 , 41 ], accompanied by ROS generation [ 42 ]. The differences in the outcome of ERK activation are probably due to differences in cellular content.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence of the anticancer activity of a variety of flavonoids [ 32 , 33 , 34 , 35 ]. Moreover, previous reports have shown flavonoid’s ability to affect the activity of specific signaling pathways, including ERK signaling, through either stimulation [ 36 , 37 , 38 , 39 ] or ERK1/2-signaling inhibition [ 40 , 41 ], accompanied by reactive oxygen species (ROS) generation [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, various in vitro and ex vivo studies have also determined the anti-tumor effects of flavonoids mediated through ERK1/2 signaling inhibition. Fisetin is one of the flavonoids that has been found to suppress ERK1/2 signaling in human gastric (SGC7901), hepatic (HepG2), colorectal (Caco-2), and pancreatic cancer cells (Suit-2) [156,157]. In human NCI-H460 NSCLC, fisetin induced ROS generation and suppressed ERK through its phosphorylation [150].…”
Section: Control Of Cancer-associated Signaling Pathways By Fisetimentioning
confidence: 99%
“…Indeed, the latter is an important regulator, since its inhibition was associated with a reduced expression of uPA and uPAR. Fisetin is another flavonoid found in fruit and vegetables that has proven to exert an inhibitory effect on the proliferation of SGC7901 cells and induced apoptosis through suppression of ERK1/2 activation [34]. Another recent study has shown how Parameritannin A2, a product extracted from the stems of the plant Urceola huaitingii, has a synergistic effect with doxorubicin in GC cells.…”
Section: Pharmaceutical Effects Of Mapk Targeting In Gastric Cancermentioning
confidence: 99%